2008
DOI: 10.1258/jrsm.2008.080337
|View full text |Cite
|
Sign up to set email alerts
|

Sudden whitening of the hair: an historical fiction?

Abstract: Sudden hair whitening (canities) was first reported centuries ago. Although a rare event, it has affected well-known historical figures, including Sir Thomas Moore and Queen Marie Antoinette of France. Early reports are substantiated by more recent cases in the scientific literature. Often, there is association with psychological stress; in the two historical cases above, the condition is thought to have been a reaction to the sentence of execution. In this paper, we examine some case histories of those afflic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Landois suggested that air in the medulla and cortex of the hair shaft created the illusion of sudden blanching of the hair. To date, microscopy has not supported either of these theories …”
Section: Progress Of This Conditionmentioning
confidence: 99%
See 4 more Smart Citations
“…Landois suggested that air in the medulla and cortex of the hair shaft created the illusion of sudden blanching of the hair. To date, microscopy has not supported either of these theories …”
Section: Progress Of This Conditionmentioning
confidence: 99%
“…On February 19, 1858, a rebel of the Bengal army was stripped naked in front of authorities, and his hair allegedly turned from jet black to gray within a half an hour as described in The Family Physician …”
Section: Historical Cases Of Canities Subitamentioning
confidence: 99%
See 3 more Smart Citations